Viaggio sulla linea dell’Aîon. La spazializzazione del tempo in Robert Smithson - Anna Longo (Aisthesis, 2012)
An images is build up of elements placed in a fix reciprocal positions. In this way an image is able to organize a block of space-time extracted from becoming and offered as a crystallized present, this notion imply Chronos notion of time. How would spatial co-ordinates work on the time line of Aîon, where present can’t exist? We are going to answer this question by analyzing Robert Smithson’s Monuments of Passaic.